Using Picture to Improve Students’ Vocabulary Mastery at SMP Negeri 3 Marioriawa - Zurgawi Zurgawi; Amirullah Abduh; Maemuna Muhayyang (State University of Makassar, 2023)
This study aims to determine whether using pictures improves students' vocabulary mastery. Using research method pre-experimental research design conducted with a sample of 27 class VII.A students using a purposive sampling technique. Researcher used pretest and posttest to collect data. The results of data analysis show that by using pictures improved students' vocabulary mastery, even though the improvement in students’ vocabulary was a slight improvement. This is evidenced by the students' mean score before treatment (48.00 points), lower than the mean score after treatment (71.62 points). Because this study's significance value (0.000) is less than its significance value (0.05), H0 in this study is rejected, whereas Ha is accepted.. So it can be concluded that using pictures can improve the vocabulary mastery of class VII.A students at SMP Negeri 3 Marioriawa.Keywords: Vocabulary Mastery, Picture